Faktor – Faktor Yang Berkorelasi Dengan Kualitas Hidup Penderita Rheumatoid Arthritis Di Poli Reumatologi SMF Penyakit Dalam RSUD Dr Soetomo Surabaya - Revantoro Artha Dwiprawira (2020)
Rheumatoid arthritis (RA) is a disease that causes inflammation with chronic and systemic properties, which are usually attacked the joints and extra-articular organs. A fairly typical symptom is pain which interferes with quality of life due to limitations in physical activity. Physical activity is usually related to the joint of the limbs and even the body, but it will be different if the disease recurs, so there will be several factors that can be related. The aim of this study was to determine the relationship between the following factors that correlate with the quality of life of patients with rheumatoid arthritis in the Rheumatology Poly of SMF Internal Medicine Hospital DR. Soetomo Surabaya. The type and design of this study is a cross-sectional analysis study using a questionnaire. Sampling with consecutive sampling technique using the Rule of Thumb formula. The variables studied were age, sex, duration of RA disease, degrees of severity of RA, and degree of quality of life disability. The method of data collection is done by completing questionnaires and interviews. Results: Of 17 study subjects, 29.41% were men, 70.59% women. In the age group 5.88% of 12-16 year olds, 5.88% 17-25 year olds, 11.76% 26-35 years old, 11.76% 36-45 years old, 23.54% of 46- 55 years old, 41.18% aged 56 to 65 years old. The severity of the patients with RA was 64.71% moderate, 35.29% severe. In the category of long-standing diagnosed RA 94.12% was ≤ 60 months, 5.88% ≥ 60 months. The degree of disability of the quality of life of patients with RA was found 41.18% mild disability, 52.94% moderate degree, 5.88% severe degree. The p-value of sex for the degree of disability of quality of life is 0.493, the p-value of age for the degree of disability of quality of life is 0.119, the p-value of the severity of the RA for quality of life disability is 0.001, the p-value for long-standing diagnosed RA for degree of quality of life disability is 0.916. The significant relationship found was only in the relationship between the severity of RA and the inability of the quality of life of patients with RA.